2010
DOI: 10.17660/actahortic.2010.883.31
|View full text |Cite
|
Sign up to set email alerts
|

Physical Methods for Soil Disinfestation in Intensive Agriculture: Old Methods and New Approaches

Abstract: Physical soil disinfestation is worldwide mainly applied in protected cropping systems or in small-scale intensive field crops. Continuous cropping of monocultures or different host plants for the same pest or pathogen often leads to heavily infested soils which forces growers to disinfest the soil thoroughly. The oldest method is steam sterilization which is applied for more than a century. In the 1970s hot water treatment of soils was developed in Japan. Hot water is applied to the soil surface to raise soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…However, flooded soil without organic amendments had no effect on reducing the number of FOC, which was in accordance with previous reports (Blok et al 2000;Goud et al 2004) that flooding or application of a plastic cover alone did not result in significant reductions of soil pathogens. The possible reason is that soil disinfestation is caused more by an indirect effect due to an increase of toxic substances produced by anaerobic microbiological activity in the soil, rather than by the lack of oxygen (Runia and Molendijk 2010). Blok et al (2000) found that pathogens were inactivated in BSD treatments as effectively with grass as with broccoli, which suggests that it is more likely that crop-nonspecific fermentation products rather than Relative abundances are based on the proportional frequencies of those DNA sequences that could be classified at the phylum level crop-specific products were involved.…”
Section: Discussionmentioning
confidence: 99%
“…However, flooded soil without organic amendments had no effect on reducing the number of FOC, which was in accordance with previous reports (Blok et al 2000;Goud et al 2004) that flooding or application of a plastic cover alone did not result in significant reductions of soil pathogens. The possible reason is that soil disinfestation is caused more by an indirect effect due to an increase of toxic substances produced by anaerobic microbiological activity in the soil, rather than by the lack of oxygen (Runia and Molendijk 2010). Blok et al (2000) found that pathogens were inactivated in BSD treatments as effectively with grass as with broccoli, which suggests that it is more likely that crop-nonspecific fermentation products rather than Relative abundances are based on the proportional frequencies of those DNA sequences that could be classified at the phylum level crop-specific products were involved.…”
Section: Discussionmentioning
confidence: 99%
“…According to Runia and Molendijk (2010), eight organic acids (acetic acid, butyric acid, maleic acid, isovaleric acid, lactic acid, citric acid, propionic acid and formic acid) were used for the screening of toxic organic acids to F. oxysporum. Erlenmeyer flask (250 ml) containing 50 g of fresh diseased sandy soil and 50 ml of organic acid solution (50 mM) were incubated at 25°C for five days.…”
Section: Screening Of Toxic Organic Acidsmentioning
confidence: 99%
“…It was supposed that toxic products derived from anaerobic decomposition of organic matter and the increased biocontrol microorganisms (Mowlick et al 2013;Momma et al 2013) rather than lack of oxygen (Runia and Molendijk 2010) or high temperature (Blok et al 2000) were involved in the mechanisms of BSD. The possible toxic products include alcohols, aldehydes, organic acids, metal ions, nitrous acid, ammonia, methane, hydrogen sulfide and other volatile compounds (Messiha et al 2007;Tenuta and Lazarovits 2002;Runia and Molendijk 2010). However, the activity of many of these toxic compounds is not fully understood, and further studies are still necessary to the precise determination (Momma et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Steam sterilization, presented as one of the alternatives to chemical methods, is the oldest physical method and has been applied for more than a century [ 9 ]. Steam treatment needs a large machine that can generate steam and introduce it into soils, and the efficiency of this method depends upon the soil type because soil temperatures are only increased in the upper soil layers in the case of sandy and loam soils [ 10 ]. Despite these obstacles, the efficiency of soil sterilization using high-temperature steam is gradually improving.…”
Section: Introductionmentioning
confidence: 99%